Pengaruh Kualitas Produk, Kualitas Pelayanan, Dan Fasilitas Terhadap Kepuasan Konsumen - Mutia, Nona; Ramadhan, Ady Tia (Jurnal Online Manajemen ELPEI, 2024)
This research aims to determine the influence of product quality, service quality and facilities on consumer satisfaction at Saung Apung Napak Sancang. This type of research is quantitative research. The population in this study were consumers who ate or had eaten at Saung Apung Napak Sancang by taking a sample of 100 consumers. This research uses Linear Regression Test analysis. Hypothesis testing uses partial tests (t) and simultaneous tests (F) with the help of SPSS version 29.0.2.0 (20). Partial test results (t) show that the variables Product Quality (X1) and Facilities (X3) have a significant effect on consumer satisfaction (Y). Meanwhile, Service Quality (X2) has no effect on Consumer Satisfaction. Simultaneous test results (F Test) show that there is a positive relationship between Product Quality, Service Quality and Facilities on Consumer Satisfaction, with an Fcount value of 63.041 > Ftable 2.703 with a significance of 0.001 < 0.05. This means that the variables Product Quality, Service Quality and Facilities jointly influence Consumer Satisfaction at Saung Apung Napak Sancang. The results of the determination test (R²) produced by the variables product quality, service quality and facilities have an effect on consumer satisfaction of 0.663 or 66.3%.